Dissolution of large intracardiac thrombus, potential role of the emerging oral fibrinolytic agent (Medical Journal of Indonesia, 2016)
Intracardiac thrombus may persist in some cases even after anticoagulant therapy. This opens a possibility to add a potent thrombolytic agent into therapeutic regimen without increasing bleeding risk any further. Increasing evidence showed a promising efficacy and safety of oral fibrin specific lumbrokinase as a thrombolytic agent. To the best of our knowledge, report of the use of lumbrokinase on intracardiac thrombus is limited. We reported two cases of intracardiac thrombi. In first patient, after two-month therapy with lumbrokinase, the previous 8 cm2 left atrial thrombus was completely disappeared. Second patient had left ventricular thrombus due to low left ventricular ejection fraction caused by coronary artery disease. A significant dissolution in thrombus size on repeated follow-up was found. Both patients did not experience any significant adverse effect. This case series aims to present the potential use of lumbrokinase as as oral antithrombotic therapy in intracardiac thrombus.